The Role of Shadow Banking for Financial Regulation - Stefan Gebauer; Falk Mazelis (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Macroprudential policies for financial institutions have received increasing prominence since the global financial crisis. These policies are often aimed at the commercial banking sector, while a host of other non-bank financial institutions, or shadow banks, may not fall under their jurisdiction. We study the effects of tightening commercial bank regulation on the shadow banking sector. For this purpose, we develop a DSGE model that differentiates between regulated, monopolistically competitive commercial banks and a shadow banking system that relies on funding in a perfectly competitive market for investments. After estimating the model using euro area data from 1999 – 2014 including information on shadow banks, we find that tighter capital requirements on commercial banks increase shadow bank lending, which may have adverse financial stability effects. In a counterfactual analysis we compare how a macroprudential policy implemented before the crisis on all financial institutions, or just on commercial banks, would have dampened the leverage cycle.
Keywords: E12; E61; F45; G23; G28; 330; Macroprudential Regulation; Shadow Banking; Financial Frictions